The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/15732479.2021.1919720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the service life, life-cycle costs and assessment of hybrid and traditional reinforced concrete through a case study of bridge edge beams in Sweden

Abstract: The edge beams of reinforced concrete bridges with de-icing salts sprayed experience extensive corrosion damage. The average service life of edge beams needing replacement in Sweden has been reported as only 45 years, causing great economic loss to both owners and users. Hence, finding a durable solution for edge beams would benefit society. Hybrid reinforced concrete structures, produced by adding a low-to-moderate fibre content into traditional reinforced concrete, can effectively limit the service crack wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Society costs are concomitant to the environmental impacts and accidents. 31 Koch et al in 2002 32 reported that approximately 15% of 583,000 bridges in the United States in 1998 were structurally deficient, primarily due to corrosion of steel and steel reinforcement. And the detailed LCCA indicated indirect cost to the user due to traffic delays and lost productivity more than 10 times of the direct costs of corrosion maintenance, repair, and rehabilitation.…”
Section: Life Cycle Cost Analysis Of Bridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Society costs are concomitant to the environmental impacts and accidents. 31 Koch et al in 2002 32 reported that approximately 15% of 583,000 bridges in the United States in 1998 were structurally deficient, primarily due to corrosion of steel and steel reinforcement. And the detailed LCCA indicated indirect cost to the user due to traffic delays and lost productivity more than 10 times of the direct costs of corrosion maintenance, repair, and rehabilitation.…”
Section: Life Cycle Cost Analysis Of Bridgesmentioning
confidence: 99%
“…Costs incurred from traffic delay and vehicle operations during the maintenance period are user costs. Society costs are concomitant to the environmental impacts and accidents 31 . Koch et al in 2002 32 reported that approximately 15% of 583,000 bridges in the United States in 1998 were structurally deficient, primarily due to corrosion of steel and steel reinforcement.…”
Section: Life Cycle Assessment Of Next Generation Aashto‐pci Bt‐72 Gi...mentioning
confidence: 99%
“…Many authors examine the life cycle costs of individual building materials, especially concrete [32][33][34]. They often focus on the link between the energy consumption needed to produce the building material and the overall environmental footprint [35][36][37] and the use of this material over its lifetime.…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…18 Furthermore, hybrid-RC has also been recently shown to be a more sustainable solution for crack control than RC from a life cycle perspective. 19 Despite the positive effects of hybrid-RC, to completely suppress corrosion is a challenging pursuit. To that end, developing tools and models to estimate the residual structural behavior of corroding RC members is crucial.…”
Section: Introductionmentioning
confidence: 99%
“… 18 . Furthermore, hybrid‐RC has also been recently shown to be a more sustainable solution for crack control than RC from a life cycle perspective 19 . Despite the positive effects of hybrid‐RC, to completely suppress corrosion is a challenging pursuit.…”
Section: Introductionmentioning
confidence: 99%